Melatonin Therapy Improves Cardiac Autonomic Modulation in Pinealectomized Patients - Campos, Luciana Aparecida; Bueno, Clarissa; Barcelos, Isabella P.; Halpern, Bruno; Brito, Leandro C.; Amaral, Fernanda G.; Baltatu, Ovidiu Constantin; Cipolla-Neto, José (Frontiers in Endocrinology, 2020)
The purpose of this investigational study was to assess the effects of melatonin replacement therapy on cardiac autonomic modulation in pinealectomized patients. This was an open-label, single-arm, single-center, proof-of-concept study consisting of a screening period, a 3-month treatment period with melatonin (3 mg/day), and a 6-month washout period. The cardiac autonomic function was determined through heart rate variability (HRV) measures during polysomnography. Pinealectomized patients (n = 5) with confirmed absence of melatonin were included in this study. Melatonin treatment increased vagal-dominated HRV indices including root mean square of the successive R-R interval differences (RMSSD) (39.7 ms, 95% CI 2.0–77.4, p = 0.04), percentage of successive R-R intervals that differ by more than 50 ms (pNN50) (17.1%, 95% CI 9.1–25.1, p = 0.003), absolute power of the high-frequency band (HF power) (1,390 ms2, 95% CI 511.9–2,267, p = 0.01), and sympathetic HRV indices like standard deviation of normal R-R wave interval (SDNN) (57.6 ms, 95% CI 15.2–100.0, p = 0.02), and absolute power of the low-frequency band (LF power) (4,592 ms2, 95% CI 895.6–8,288, p = 0.03). These HRV indices returned to pretreatment values when melatonin treatment was discontinued. The HRV entropy-based regularity parameters were not altered in this study, suggesting that there were no significant alterations of the REM–NREM ratios between the time stages of the study. These data show that 3 months of melatonin treatment may induce an improvement in cardiac autonomic modulation in melatonin-non-proficient patients. ClinicalTrials.gov Identifier: NCT03885258.